Delivery Profile and indications of Cesarean Section in a rural referral Hospital: what could be the implications? - Shrestha, U.; Aryal, Binod (Journal of Karnali Academy of Health Sciences, 2018)
Introduction: There is huge difference in cesarean section rate between rural (3.5%) and urban (15%) areas of Nepal. The national CS rate is around 5% whereas global CS rate is 26%. The objective of this study is to find out the delivery profile and rate and indications of CS in a rural university hospital.Methodology: This is a three -year’s retrospective cross-sectional study done from January 2016 to January 2019 (Magh 2072 to Poush 2075) at Karnali Academy of Health Sciences, Jumla. The data was retrieved from hospital birth profile records and analyzed using SPSS 20. Permission was taken from Institutional review committee (IRC) to conduct the study.Results: Total number of delivery during this period was 1841 out of which 172 were Cesarean delivery giving a CS rate of 9.3%. The most common indication of CS were fetal distress (33.7%), previous CS (9.3%), failed induction of labor (9.3%). Non progress of Labor (8.1%) and post term pregnancy (8.1%). Majority of the CS were done as an emergency procedure.Conclusion: The CS rate at KAHS teaching hospital was within WHO recommendation of between 5-15% and was very low in comparison to other centers situated in urban areas of the country. The indications of CS was also similar to the other national and international statistics.